Complement activation in patients with isolated antiphospholipid antibodies or primary antiphospholipid syndrome - Breen, Karen A.; Seed, Paul; Parmar, Kiran; Moore, Gary W.; Stuart-Smith, Sara E.; Hunt, Beverley J. (Thrombosis and Haemostasis, 2012)
The antiphospholipid syndrome (APS) is the association of thrombosis and recurrent pregnancy loss and/or pregnancy morbidity with persistent antiphospholipid antibodies (aPL). Increased complement activation has been implicated in the pathogenesis of APS in animal models. It was our objective to evaluate complement activation in patients with aPL or primary antiphospholipid syndrome (PAPS). We measured complement activation products, fragments Bb and C3a–desArg by ELISA in 186 aPL/PAPS patients and 30 healthy controls. All patients with aPL had significantly increased levels of complement activation products. Fragment Bb levels (mean, 95% CI); (thrombotic APS 0.54 units/ml, 0.31–0.83, obstetric APS 0.60 units/ml,0.39–1.02, isolated aPL 0.48 units/ml, 0.29–0.85, overall 0.39 units/ml, 0.33–0.47) and C3a–desArg levels (mean, 95% CI): (thrombotic APS 261 ng/ml, 219–311, obstetric APS 308 ng/ml, 243–391, isolated aPL 258 ng/ml, 193–337, overall 225 ng/ml, 202–251) were significantly higher compared to controls (fragment Bb 0.06 units/ml, 0.03–0.11, C3a–desArg 69 ng/ml, 50–92). There were correlations between Fragment Bb and C3a–desArg levels in all patients with aPL. Receiver operator characteristic (ROC) analysis showed increased fragment Bb and C3a–desArg levels had strong associations with the presence of persistent lupus anticoagulant (area under ROC: Bb 0.89, and C3a–desArg 0.90), dual and triple aPL positivity (Bb 0.71–0.82, C3a–desArg 0.71–0.80) but not with high titre anti-cardiolipin antibodies (Bb 0.62, C3a–desArg 0.65), or anti β2-glycoprotein 1 antibodies (Bb 0.66, C3a–desArg 0.67). Complement activation is present in all patient groups within this large cohort of patients aPL. This suggests it may have a major role in the pathogenesis of APS and merits further study.
Keywords: Antiphospholipid antibodies; antiphospholipid syndrome; complement activation